Brief Report: High Rates of Adverse Birth Outcomes in HIV and Syphilis Coinfected Women in Botswana. (15th August 2019) - Shava, Emily; Moyo, Sikhulile; Zash, Rebecca; Diseko, Modiegi; Dintwa, Eldah N.; Mupfumi, Lucy; Mabuta, Judith; Mayondi, Gloria; Chen, Jennifer Y.; Lockman, Shahin; Mmalane, Mompati; Makhema, Joseph; et al.
Abstract : Background: Little is known about the combined impact of HIV/syphilis coinfection on birth outcomes. Methods: Antenatal HIV and syphilis test results, obstetric history, and infant birth outcomes were collected from obstetric records in maternity wards in Botswana between 2008 and 2011 (5 sites) and 2014 and 2016 (8 sites). We used logistic regression to compare adverse birth outcomes by HIV and syphilis status. Outcomes included stillbirth, preterm delivery, low birth weight, and in-hospital neonatal death. Results: Of 76, 466 women, 75, 770 (99.1%) had HIV test results, and 20, 520 (27.1%) were HIV positive. Syphilis test results were available for 67, 290 (88.0%), and 697 (1.0%) had reactive rapid plasma reagin. Among 692 women with syphilis and an HIV test result, 261 (37.7%) were coinfected. HIV-infected women were more likely to be infected with syphilis than HIV-uninfected women [odds ratio (OR) = 1.68; 95% confidence interval (CI): 1.44 to 1.96]. From 2008–2011 to 2014–2016, the proportion of women with syphilis remained constant (1.1% vs. 1.0%, P = 0.41), but HIV/syphilis coinfection declined from 45% to 27% ( P < 0.0001). Stillbirth occurred in 5.8% of coinfected women, compared with 1.9% with no HIV/syphilis (OR = 3.09; 95% CI: 1.83 to 5.23); 3.4% with HIV alone (OR = 1.75; 95% CI: 1.03 to 2.97), or 3.7% with syphilis alone (OR = 1.58; 95% CI: 0.77 to 3.25). Low birth weight occurred in 24.1% of coinfected women, compared with 12.1% with no HIV/syphilis (OR 2.31; 95% CI: 1.74 to 3.08; 20% with HIV alone (OR = 1.27; 95% CI: 0.96 to 1.69); or 14.6% with syphilis alone (OR = 1.85; 95% CI: 1.26 to 2.74). Conclusions: Although HIV/syphilis coinfection in pregnancy has declined in the past decade, coinfection was associated with adverse birth outcomes.